Arp2/3 Complex Is Required for Auxin-Driven Cell Expansion Through Regulation of Auxin Transporter Homeostasis - García-González, Judith; Kebrlová, Štépánka; Semerák, Matěj; Lacek, Jozef; Kotannal Baby, Innu; Petrášek, Jan; Schwarzerová, Kateřina (Frontiers in Plant Science, 2020)
The Arp2/3 complex is an actin nucleator shown to be required throughout plant morphogenesis, contributing to processes such as cell expansion, tissue differentiation or cell wall assembly. A recent publication demonstrated that plants lacking functional Arp2/3 complex also present defects in auxin distribution and transport. This work shows that Arp2/3 complex subunits are predominantly expressed in the provasculature, although other plant tissues also show promoter activity (e.g. cotyledons, apical meristems or root tip). Moreover, auxin can trigger subunit expression, indicating a role of this phytohormone in mediating the complex activity. Further investigation of the functional interaction between Arp2/3 complex and auxin signaling also reveals their cooperation in determining pavement cell shape, presumably through the role of Arp2/3 complex in the correct auxin carrier trafficking. Young seedlings of arpc5 mutants show increased endogenous auxin levels and altered PIN3 distribution, with higher levels of the protein in the vacuole. Closer observation of vacuolar morphology revealed the presence of a more fragmented vacuolar compartment when Arp2/3 function is abolished, hinting a generalized role of Arp2/3 complex in endomembrane function and protein trafficking.